Corporate Social Responsibility: Not An Option But An Obligation For All Business (Trinity Journal of Management, IT & Media (TJMITM), 2014)
This paper will give the meaning of the CSR and recognize some of the  factors that led to the emergence of corporate social responsibility. It  will also discuss the importance of corporates setting up corporate  social responsibility projects, and the impact these have on their  performance and society as well.
Keywords: Obligation; CSR; corporate social responsibility projects; performance and society